Civilian Warriors : The Inside Story of Blackwater and the Unsung Heroes of the War on Terror - Prince, Erik and Coburn, Davin (New York Penguin Group, 2013)
The founder of Blackwater, the world's most controversial military contractor, describes how the company took on high-risk security jobs around the world, completing nearly 100,000 missions in Afghanistan and Iraq, only to have opponents tarnish their reputation
Keywords: Blackwater USA -- History -- Terrorismus -- Civil-military relations